Maryna Cherkashіna as librettist: «musical theatre expressed in words» - Drach, Iryna (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2025)
The relevance of the study. In the history of Ukrainian culture, the prominent personality of Maryna Cherkashіna-Gubarenko (1938–2024) occupied a significant place as a musicalogist, leader of Ukrainian opera studies, music and theatre critic, journalist, teacher, scientific expositor of modern art and tireless educator. Her legacy also includes several poetry collections and ten opera libretti, among which eight were embodied by the composer, and six operas on her libretti were staged. As literary sources, she used the works of William Shakespeare, St. Francis of Assisi, Mykola Hohol, Hryhorii Kvitka-Osnovianenko, Taras Shevchenko, Prosper Mérimée, Jules Verne, Mykola Kulish, Oleksandr Korneichuk, and Vasyl Bykov. Her work on libretti was not of secondary importance among her life and artistic priorities since it was existentially motivated and revealed as an integrative act of sublimation of the entire set of her life, research and artistic experience. Understanding this unique experience determines the topicality of this article. Main objective of the study is the specifics of the librettist’s work in modern Ukrainian theater. The methodology includes biographical (to clarify the circumstances of Maryna Cherkashina-Gubarenko’s life and work), comparative (to identify the continuity of libretto texts in relation to previous examples of the genre), as well as a complex of analytical approaches, including structural-functional, genre-stylistic, narratological, lexical, and dramaturgical (to characterize selected examples of libretto creativity). Results and conclusions. It is emphasize to characterise the libretto work of Maryna Cherkashіna-Gubarenko as a body of texts in the aspect of the opera tradition, as well as to identify the specifics of her work on the opera libretto as a project and meta-referential artefact using cases in point. The purpose of this article is Cherkashіna’s libretto heritage became the object of research for the first time, which allowed not only to complement the vision of the history of Ukrainian opera of the last decades of the XX century, but also to test modern approaches to the study of opera libretto as an independent literary genre. Using the example of two texts, ‘Seven Words of Malachi’ (Singspiel libretto) and ’The Children of Captain Grant’ (opera libretto), the features of constructing an opera composition as a network of meta-literary, meta-theatrical and meta-musical connections in the levels of potentiality incorporated into the project are characterised. Historical continuity in the selection and combination of opera topoi, appealing to Gioacchino Rossini as comedy dramatist, is determined.